Autoantibody-mediated arthritis in the absence of C3 and activating Fcγ receptors: C5 is activated by the coagulation cascade - Auger, Jennifer L (BioMed Central, 2012)
INTRODUCTION: The effector functions of immunoglobulin G (IgG) are mediated by interaction of its Fc region with Fc receptors (FcγRs) and/or the complement system. The three main pathways of complement activation converge at C3. However, C3-independent pathways can activate C5 and other downstream complement components during IgG-initiated inflammatory responses. These C3-independent pathways of C5 activation are triggered by activating FcγRs in some systems or can be activated by factors of the coagulation cascade such as thrombin. Here we studied the interplay of C3, C5, and activating FcγRs in a model of spontaneous autoantibody-driven arthritis. METHODS: We utilized the K/BxN TCR transgenic mouse model of arthritis. We bred K/BxN mice bearing targeted or naturally-occurring mutations in one or more of the genes encoding complement components C3, C5, and FcRγ, the cytoplasmic signaling chain shared by the activating FcγRs. We measured arthritis development, the production of arthritogenic autoantibodies, T cell activation status and cytokine synthesis. In addition, we treated mice with anti-C5 monoclonal antibodies or with the thrombin inhibitor argatroban. RESULTS: We have previously shown that genetic deficiency of C5 protects K/BxN mice from the development of arthritis. We found here that C3-deficient K/BxN mice developed arthritis equivalent in severity to C3-sufficient animals. Arthritis also developed normally in K/BxN mice lacking both C3 and FcRγ, but could be ameliorated in these animals by treatment with anti-C5 monoclonal antibody or by treatment with argatroban. Production of arthritogenic autoantibodies, T cell activation, and T cell cytokine production were not affected by the absence of C3, C5, and/or FcRγ. CONCLUSIONS: In K/BxN mice, C5-dependent autoantibody-driven arthritis can occur in the genetic absence of both complement C3 and activating FcγRs. Our findings suggest that in this setting, thrombin activates C5 to provoke arthritis.